PERBANDINGAN ANTARA KADAR VITAMIN C PLASMA DARAH HAMIL ATERM PADA KETUBAN PECAH DINI DENGAN HAMIL ATERM TANPA KETUBAN PECAH DINI - Defrin Defrin; Rosfita Rasyid (Andalas Obstetrics And Gynecology Journal, 2018)
Premature rupture of membranes is the most common complication of pregnancy. The incidence of premature rupture of membranes in pregnancy ranged from 6% to 10%, and 20% of these cases occur before 37 weeks gestation. The incidence of premature rupture of membranes in Indonesia ranges from 4.5% to 7.6% of all pregnancies. This research was conducted to determine the cross-sectional differences in the blood plasma levels of vitamin C in term pregnancy premature rupture of membranes with blood plasma levels of vitamin C in term pregnancy without premature rupture of membranes in M. Jam- il Padang hospital, Achmad Muchtar Bukittinggi hospital, and Pariaman Hospital. There are significant differences in vitamin C blood plasma levels in term pregnancy with premature rupture of membranes and term pregnancy without premature rupture of membranes ( P < 0.05). Mean levels of vitamin C in blood plasma at term pregnancy with premature rupture of membranes lower than in the blood plasma levels of vitamin C in term pregnancy without premature rupture of membranes.Keywords: Premature rupture of membrane in aterm, blood plasma levels of vitamin C